Faktor- Faktor Yang Berhubungan Dengan Cakupan Persalinan di fasilitas Pelayanan Kesehatan Wilayah Kerja Puskesmas Rantau Suli Tahun 2023 - Dwi Gustin Franciska; Eltriya Septiyani (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
Background: Giving birth in a Health Service Facility is a recommendation from the government to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), the legal basis is stated in Permenkes no. 97 of 2014 article 14 paragraph (1) which states "delivery must be carried out in a Health Service Facility (fasyankes). In Permenkes No. 39 of 2016 concerning Healthy Family Indicators. In indicator number two, namely "mothers carry out the delivery process in a Health Service Facility". Research Method: The type of research uses a quantitative analytical type with a cross-sectional design. The population is 36 people and the sample is the total population. Data was collected through a questionnaire. Data were analyzed univariately and bivariately using the chi-square test Results: The results of the statistical test of maternal knowledge with P_value = 0.030, attitudes with P_value = 0.012, education with P_value = 0.018 and economic level with P_value = 0.001. Conclusion: There is a relationship between the level of knowledge, attitude, education, and economic status in the Rantau Suli Health Center Work Area in 2023. It is hoped that the Rantau Suli Health Center, especially health workers, will increase counseling activities about childbirth at Health Service Facilities.